Muhammad Iqbalâ€™s Philosophy of Religion and Politics: The Basic Concept of Religious Freedom - Muhammad Saleh Tajuddin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
The objective of this writing is to explore Iqbalâ€™s thought about religion and politics as the basic concepts of religious freedom. This writing is done by doing research in library and running qualitative research based on philosophical approach. The study is analyzed through descriptive analysis to get accurate results from the objective of the study. The results of the research are: 1) Iqbalâ€™s thought of religion is based on creed (belief), which reflects on rational thought. Iqbalâ€™s effort on reconstruction of religion gives harmony between religion and politics which leads to the society too. 2) The religious freedom from Iqbalâ€™s thought is based on the political ethics concept. His idea is started with the integration between Western thoughts and the Qurâ€™an. Iqbalâ€™s perspective of ego promotes self freedom, so every person can avoid his self from getting perfect spiritual (insane kamil). 3) Individual that lives in â€œreality as self consciousâ€ concerns on the powers, which will create a harmony to society.